Setting the captives free : the Bible and human trafficking - Carson, Marion L. S. (Cambridge, United Kingdom : The Lutterworth Press, 2016)
"Marion Carson sets out to answer the question, what does the Bible say about human trafficking? Aimed at Christian anti-trafficking activists and church groups, the book offers an overview of the biblical material on slavery and the sex trade. Acknowledging that there is a difference between the biblical worldview and most Christians today with regard to slavery, it suggests that we can learn much from the Abolitionists of the eighteenth and nineteenth centuries. Following their example, it reads the biblical text through the lens of the law of love. Each chapter provides study questions and is illustrated throughout."--
Introduction -- Human trafficking today -- Reading the Bible: lessons from history -- Slavery in the Old Testament -- Slavery in the New Testament -- Prostitution in the Old Testament -- Prostitution in the New Testament -- Conclusion.
Includes bibliographical references (pages 101-105).
PDF (JSTOR, viewed Apr. 24, 2017).
Keywords: Human trafficking -- Religious aspects -- Christianity; Human trafficking -- Religious aspects -- Judaism; Slavery in the Bible; Slavery -- Religious aspects -- Christianity; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; Electronic books